1998
DOI: 10.1557/proc-512-475
|View full text |Cite
|
Sign up to set email alerts
|

Doping of GaN by Ion Implantation: Does it Work?

Abstract: SS.;5'Epitaxially grown GaN by metal organic chemical vapor deposition (MOCVD) on Si were implanted with 100 keV Si' (for n-type) and 80 keV Mg' (for p-type) with various fluences from 1 x 1 0l2 to 7x1 015 ions/cm2 at liquid nitrogen temperature (LT), room temperature (RT), and 700 O C (HT). High temperature (1200 O C and 1500 OC) annealing was carried out after capping the GaN with epitaxial AIN by MOCVD to study damage recovery. Samples were capped by a layer of AlN in order to protect the GaN surface during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The apparent recovery of detected luminescence by such annealing, which has been observed experimentally, 2,13,21,[45][46][47][48][49] has been attributed to ͑i͒ thermally induced recovery of lattice defects that enhance the absorption of light within the implanted layer and ͑ii͒ recovery of CL emission in the ion end-of-range region, where the concentration of implantation-produced defects is sufficiently low so that most of these defects can be effectively removed by such annealing. 49 Indeed, previous studies 49 have shown that CL emission is restored in the ion end-of-range region, where the level of implantation disorder is relatively low, but the concentration of implanted species is relatively high.…”
Section: B Thermal Annealing Of Implantation Damagementioning
confidence: 99%
“…The apparent recovery of detected luminescence by such annealing, which has been observed experimentally, 2,13,21,[45][46][47][48][49] has been attributed to ͑i͒ thermally induced recovery of lattice defects that enhance the absorption of light within the implanted layer and ͑ii͒ recovery of CL emission in the ion end-of-range region, where the concentration of implantation-produced defects is sufficiently low so that most of these defects can be effectively removed by such annealing. 49 Indeed, previous studies 49 have shown that CL emission is restored in the ion end-of-range region, where the level of implantation disorder is relatively low, but the concentration of implanted species is relatively high.…”
Section: B Thermal Annealing Of Implantation Damagementioning
confidence: 99%
“…Recent ion-implantation studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] have revealed that, unlike the situation for mature semiconductors such as Si and GaAs, GaN exhibits a range of intriguing behavior involving extreme property changes under ion bombardment. 19 In particular, it has been shown that dynamic annealing processes ͑i.e., defect-interaction processes͒ in GaN are extremely efficient even during heavy-ion bombardment at liquid-nitrogen temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Parikh et al 3 reported Rutherford backscattering/channeling ͑RBS/C͒ and crosssectional transmission electron microscopy ͑XTEM͒ studies of GaN bombarded with 120 keV Mg and 160 keV Si ions at 550°C. Suvkhanov et al 4 reported a RBS/C study of GaN bombarded at 700°C with 100 keV Si and 80 keV Mg ions. Another report on lattice disorder produced by a moderate dose of 90 keV Mg ions implanted into GaN at temperatures up to 550°C and studied by RBS/C was reported by Wenzel, Liu, and Rauschenbach.…”
mentioning
confidence: 99%
“…After implantation, samples were characterized ex situ by RBS/C with 1.8 MeV 4 He ϩ ions incident along the ͓0001͔ direction and backscattered into a detector at 98°relative to the incident beam direction to provide enhanced depth resolution for examining near-surface damage accumulation. XTEM was performed in a Philips CM12 transmission electron microscope operating at 120 keV.…”
mentioning
confidence: 99%